2021
DOI: 10.4315/jfp-20-402
|View full text |Cite
|
Sign up to set email alerts
|

Induction of a Viable but Nonculturable State, Thermal and Sanitizer Tolerance, and Gene Expression Correlation with Desiccation-Adapted Biofilm and Planktonic Salmonella in Powdered Infant Formula

Abstract: This study investigated the effects of the physiological state, desiccation-adaptation, and storage of powdered infant formula (PIF) on Salmonella survival and their desiccation stress-related gene expression. PIF was inoculated with S . Typhimurium in the biofilm state on beads and in the planktonic state on nitrocellulose filters and stored at 25°C for up to 270 days. 5-cyano-2,3-ditoyl tetrazolium chloride flow cytometry (CTC-FCM) and Xylose Lysine Deoxycholate (XLD) plate count experiments demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Our study revealed that heat treatment had a notable impact on the gene expression levels of isolates, as the RNA expression level in the treated isolates differed significantly from that of the untreated or negative controls. This finding is consistent with the results reported by Chen et al [ 49 ], who also investigated the effect of heat treatment on gene expression in various isolates before and after treatment.…”
Section: Discussionsupporting
confidence: 93%
“…Our study revealed that heat treatment had a notable impact on the gene expression levels of isolates, as the RNA expression level in the treated isolates differed significantly from that of the untreated or negative controls. This finding is consistent with the results reported by Chen et al [ 49 ], who also investigated the effect of heat treatment on gene expression in various isolates before and after treatment.…”
Section: Discussionsupporting
confidence: 93%
“…It was made of wood (with small pores and fine cracks) and remained at least 8 months a year covered by a dried milk layer. These factors favored the long-term survival of some of the microbes that inhabited and were able to remain alive within the desiccation-adapted biofilms [9]. It has been shown that some microbes, including foodborne pathogens, can resist drying processes and survive for long periods in lowmoisture foods and environments, especially after exposure to non-lethal stress conditions, such as sub-lethal acidic or salty environments, which are present during cheese production, and, eventually, can grow if the dry food is rehydrated [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Since such well-preserved cheese seals are rare, and vegetative bacterial cells may survive desiccation for long periods, particularly when protected by milky environments [6][7][8][9], the objectives of this work were, first, to submit the dairy crust to an enrichment step in order to know if culturable lactic acid bacteria remained in the seal and, if it was the case, then undertake a preliminary in vitro and in silico characterization of the isolated strain(s). In parallel, a metataxonomic analysis of this old biological material was also performed to explore which bacterial species might have been originally present in the seal.…”
Section: Introductionmentioning
confidence: 99%
“…The prepared bacterial suspensions of S. Enteritidis were referred to as the 0-samples. Dehydration and SMP storage of Salmonella were performed as previously described in the literature (Chen et al, 2021). First, the silica gels were initially dehydrated in a 108°C oven to ensure complete water removal and irradiated with UV light for 30 min to kill the background bacteria.…”
Section: Desiccation and Milk Powder Storagementioning
confidence: 99%